Development of Maintenance Management System Based on Web Application of Faculty of Pharmacy, Mahidol University - ทัศนเจริญ โสรัจ; แสงงาม ชาญเดช; วูดเด่น สิริมา; โขมะสรานนท์ อรพรรณ์; จินากุล นันทวรรณ (Journal of Applied Research on Science and Technology (JARST), 2018)
This study was aimed to 1) develop a maintenance management system based on web application 2) evaluate the period for completion of maintenance on web application based on the model system development life cycle (SDLC). This system was divided into five phases: 1) planning 2) analysis 3) design 4) application and 5) maintenance. Then, the completion period of maintenance was determined by the collection of 895 documents during October 1, 2013 - September 30, 2014. The statistics used were the mode, percentages and averages. The results showed that 1) the developed system was able to track the status of the repair, history and results of operations, which could be adapted to develop maintenance management system on web application of the Faculty of Pharmacy, Mahidol University 2) the period for completion of maintenance on web application showed that the period of the repair of electrical systems, air conditioning systems, plumbing systems and system building, had average completion periods per item of 3.85, 3.75, 2.73 and 4.08, respectively. Completion period with the highest frequency in the repair list was 1 day of every system. Development of maintenance management system based on web application allows for more efficient maintenance and can be used to plan the administration to improve the service for the better. It can be taken as a model in the development of management systems in other departments in the future.